THE POTENTIAL OF ARTHROPODE DIVERSITY FOR ECOTOURISM DEVELOPMENT IN WONOREJO MANGROVE ECOSYSTEM, SURABAYA - Nova Maulidina Ashuri; Abdul Azis; Noor Nailis Sa’adah (UPT Penerbitan Universitas Jember, 2016)
Mangrove ecosystems all along coastal area has a lot of benefits, such as home for coastal animals (fishes and insects) and acting as coastal line protector. One of the biggest mangrove ecosystem in Surabaya is Wonorejo, which now not only act as mangrove preservation but also becoming one of eco-tourism destination in East Java. Tourists are usually come to take photos, fishing, enjoying the birds chirping and the ambience of mangrove forest. Beside that, Wonorejo also becoming one of research object for mangrove ecosystem in East Java. Several research has been done, such as research to examine mangorve diversity, birds, fishes and crabs. One of the research that hasn’t been done is about Arthropods, especially in the class of Insects and Arachnids. In this paper, the potentiality of Arthropods diversity all along Wonorejo Ecotourism Area will be examined and researched. The results will be used as alternative in order to develop educational function in this area. Tourists will not only be enjoying the ambience and take photos, but also they will have educational experience when visiting Wonorejo. Arthropode samples from several Ordos, such as Diptera, Hymenoptera, Lepidoptera, Odonata, Coleoptera, Hemiptera, Orthoptera and Araneae have taken on June 2016 in Wonorejo Ecotourism Area using sweepnet and hands collecting methods. All of those sample then have examined in Zoology and Animal Engineering Laboratory at Institut Teknologi Sepuluh November, Surabaya. Then, the data will be used as the background to develop Wonorejo tourism potentials, especially in educational form.